2014
DOI: 10.1016/j.chroma.2014.09.085
|View full text |Cite
|
Sign up to set email alerts
|

Instrument parameters controlling retention precision in gradient elution reversed-phase liquid chromatography

Abstract: The precision of retention time in RPLC is important for compound identification, for setting peak integration time windows and in fundamental studies of retention. In this work, we studied the effect of temperature (T), initial (ϕ0) and final mobile phase (ϕf)composition, gradient time (tG), and flow rate (F) on the retention time precision under gradient elution conditions for various types of low MW solutes. We determined the retention factor in pure water (k′w) and the solute-dependent solvent strength (S)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 17 publications
(8 citation statements)
references
References 54 publications
0
8
0
Order By: Relevance
“…Additionally, the shift of retention time of HSF that appeared in Figure 1b,d, could be related to temperature fluctuation or column contamination and fouling of the guard column. (Beyaza et al, 2014). However, the pattern of peak shifting was quite constant and this contributed to ensure that those peaks corresponded to the peaks of our target compounds.…”
Section: Hplc Chromatogram and Chemical Contents Of Hsf Of Purple Rmentioning
confidence: 99%
“…Additionally, the shift of retention time of HSF that appeared in Figure 1b,d, could be related to temperature fluctuation or column contamination and fouling of the guard column. (Beyaza et al, 2014). However, the pattern of peak shifting was quite constant and this contributed to ensure that those peaks corresponded to the peaks of our target compounds.…”
Section: Hplc Chromatogram and Chemical Contents Of Hsf Of Purple Rmentioning
confidence: 99%
“…And the analytes dissolved in a weak elution solvent would be stacked on the head of the UHPLC column until the LC gradient changed for the following separation . The ratio of the organic phase to the aqueous phase depended on the elution efficiency of the organic phase and the character of the analytes . Several ratios of Pump A to Pump B that presented the dilution ratio were tested in this study, and 92% of Pump A ratio was finally chosen based on both the column‐head stacking effect and the dilution time.…”
Section: Resultsmentioning
confidence: 99%
“…(12) (15), which predict decreasing k e at increasing starting concentrations of ACN, A. At a constant gradient time, t G = t, however, increasing A is automatically connected with decreasing gradient slopes, B:…”
Section: Modeling Gradient Separationmentioning
confidence: 96%
“…The re-equilibration can occur quickly, with less than three column volumes of conditioning solvent for flushing out the system dwell volume, V D , and the column hold-up volume, V M [14]. Recent investigation confirmed that gradient retention times are less sensitive to minor fluctuations in flow rate, temperature and mobile phase composition in comparison with isocratic data [15].…”
Section: Introductionmentioning
confidence: 94%